Don’t ask, don’t tell ? the ethics of disclosure of HIV-status to perinatally-infected children - Santis, Joseph De; Colin, Jessie M. (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: The care of children with Human Immune Deficiency Virus (HIV) infection in the United States has become an area of concern for pediatric health care providers. Perinatal, or mother to child infection accounts for about 90 percent of all HIV cases in children. Objective: Thecare of children with Human Immune Deficiency Virus (HIV) infection in the United States has become an area of concern for pediatric health careproviders. The objectives of this paper is to identify some of the reasons why parents do not disclose HIV-status to children; to discuss the specialchallenges for health care providers such as registered nurses (RNs) and pediatric nurse practitioners (PNPs) who provide care for HIV-infected chil-dren; and to discuss the ethical challenges which must be addressed by health care professionals. Methods:This paper uses a case study approach topresent the complex ethical issue of disclosure of the diagnosis of perinatally-acquired HIV to a child against the wishes of the child’s parents. Results: Based on the ethical principles, RNs and PNPs should adopt a stance that support disclosure at a certain point in the child/adolescent’s life. Disclosure of HIV status is a stressful experience for the parent, child, and the healthcare provider who performs the disclosure. Disclosure, there fore, needs to occur as a process. Conclusion: Disclosure of diagnosis to an HIV-infected child is a difficult issue for healthcare providers and forparents. Each institution that provides care for HIV-infected children should have a protocol in place for handling this complex issue. Although avariety of other factors besides ethics need to be considered, ethics provide a starting point for grappling with this complex issue. As professionalsproviding care for children, it is important that the best interest of the child is at the center of the decision making proces.